The effect of blending ratio and baking temperature on the physicochemical and sensory properties of biscuit from wheat and ground nut flour - Zemenu Tadesse Adimas; Aderaye Jembere Alemayehu; Biresaw Demelash Abera (Applied Food Research)
Biscuits, a widely consumed bakery product, primarily utilize wheat flour as their main ingredient, yet this ingredient possesses limited nutritional benefits (lacks essential amino acids, fiber, and micronutrients); thus, utilizing composite flours derived from legumes and various cereals can enhance their nutritional profile. The aim of this study was to mitigate the limitation of wheat flour by substituting the groundnut flour, and effect of baking temperature on the quality of biscuit. The biscuit production was carried out by using a two factors: substitution of groundnut flour (BR0 = 100: 0 %, BR1, = 90: 10 %, BR2, = 80: 20 %, and BR3 = 75: 25 % wheat: groundnut flour) and baking temperature (T1 = 210 °c, T2 = 230 °c, and T3 = 250 °c). The physicochemical content and sensory attributes of the biscuit samples were determined. The highest mean values of the protein, fat, ash, and fiber of biscuit 14.90 ± 0.63, 16.44 ± 0.76, 1.98 ± 0.02 and 2.96 ± 0.23, respectively were obtained in the treatment BR3T1, and other physical and sensory properties of biscuit were increased with amount of substitution of groundnut flour while they decreased with baking temperature. The use of groundnut flour in biscuit production can significantly improve the biscuit's nutritional and sensory properties. The study suggests a 25 % groundnut flour blending ratio and 210°C baking temperature for improved biscuits with enhanced nutritional values (the protein, crude fat, and total dietary fiber) and sensory properties such as taste, aroma, color, and flavor.